2021
DOI: 10.1097/cad.0000000000001083
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of circ_0078607 prevents development of gastric cancer and inactivates the ERK1/2/AKT pathway through the miR-188-3p/RAP1B axis

Abstract: The aim of this study is to explore the expression and mechanism of circ_0078607 on proliferation and apoptosis of gastric cancer. Real time PCR (RT-PCR) was performed to detect the expression of circ_0078607 in gastric cancer tumor tissues, plasma and cell lines. Cell viability was detected by cell counting Kit-8. Cell proliferation ability was assessed by cell cycle assay. The samples were analyzed by flow cytometry for the detection of apoptosis. Luciferase assay and RNA immunoprecipitation (RIP) were carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The competing endogenous RNA (ceRNA) theory suggested that circRNA regulated gene expression through sponge miRNAs 1 . Previous studies had shown that miR‐188‐3p played an important role in cancers such as hepatocellular carcinoma, 24 breast cancer, 25 and gastric cancer 26 . In PE, miR‐188‐3p had been reported to be down‐regulated, but its effect on PE has not been investigated 21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The competing endogenous RNA (ceRNA) theory suggested that circRNA regulated gene expression through sponge miRNAs 1 . Previous studies had shown that miR‐188‐3p played an important role in cancers such as hepatocellular carcinoma, 24 breast cancer, 25 and gastric cancer 26 . In PE, miR‐188‐3p had been reported to be down‐regulated, but its effect on PE has not been investigated 21 .…”
Section: Discussionmentioning
confidence: 99%
“…1 Previous cers such as hepatocellular carcinoma, 24 breast cancer, 25 and gastric cancer. 26 In PE, miR-188-3p had been reported to be down-regulated, but its effect on PE has not been investigated. 21 Our results also confirmed that the expression level of miR-188-3p in PE placenta was lower than that in normal placenta.…”
Section: Discussionmentioning
confidence: 99%
“…The network analysis indicated that the ERK1/2/AKT pathway was involved in the metastasis of gastric cancer. 67 Circ-Rangap1 was found to be highly expressed in the plasma of patients with gastric cancer. Its high expression was positively correlated with TNM stage and advanced lymph node metastasis.…”
Section: Gastric Cancermentioning
confidence: 99%
“…Circ_0078607 has been reported to control tumorigenesis and regulate proliferation and migration in human cancers. Downregulation of circ_0078607 blocked the gastric cancer development and induced the inactivation of the ERK1/2 and Akt pathways via targeting the miR-188-3p and RAP1B ( Bian et al, 2021 ). Circ_0078607 has been found to repress tumor progression via modulating the miR-518a-5p and Fas signaling pathway in ovarian cancer ( Zhang et al, 2020c ).…”
Section: Role Of Circrnas In Drug Resistancementioning
confidence: 99%